NUT carcinoma in children and adults: A multicenter retrospective study. Issue 12 (23rd June 2017) - Lemelle, Lauriane; Pierron, Gaëlle; Fréneaux, Paul; Huybrechts, Sophie; Spiegel, Alexandra; Plantaz, Dominique; Julieron, Morbize; Dumoucel, Sophie; Italiano, Antoine; Millot, Fréderic; Le Tourneau, Christophe; Leverger, Guy; et al.
Abstract: Background: Nuclear protein of the testis ( NUT ) carcinoma (formerly NUT midline carcinoma) is an aggressive tumor defined by the presence of NUT rearrangement with a poor prognosis. This rare cancer is underdiagnosed and poorly treated. Objective: The primary objective of this study was to describe the clinical, radiologic, and biological features of NUT carcinoma. The secondary objective was to describe the various treatments and assess their efficacy. Methods: This retrospective multicenter study was based on review of the medical records of children and adults with NUT carcinoma with specific rearrangement or positive anti‐NUT nuclear staining (>50%). Results: This series of 12 patients had a median age of 18.1 years (ranges: 12.3–49.7 years). The primary tumor was located in the chest in eight patients, the head and neck in three patients, and one patient had a multifocal tumor. Nine patients presented regional lymph node involvement and eight distant metastases. One‐half of patients were initially misdiagnosed. Specific NUT antibody was positive in all cases tested. A transient response to chemotherapy was observed in four of 11 patients. Only two patients were treated by surgery and five received radiotherapy with curative intent. At the end of follow‐up, only one patient was still in remission more than 12 years after the diagnosis. Median overall survival was 4.7 months (95% confidence interval [CI]: 2.1–17.7). Conclusion: NUT carcinoma is an aggressive disease refractory to conventional therapy. Early diagnosis by NUT‐specific antibody immunostaining in cases of undifferentiated or poorly differentiated carcinoma to identify the specific rearrangement of NUT gene is useful to propose the optimal therapeutic strategy.